Maternal exposure of rats to sodium saccharin during gestation and lactation on male offspring† - Godoi, Alana Rezende [UNESP]; Fioravante, Vanessa Caroline [UNESP]; Santos, Beatriz Melo [UNESP]; Martinez, Francisco Eduardo [UNESP]; Pinheiro, Patricia Fernanda Felipe [UNESP] (Oxford University Press (OUP), 2023)
We investigated the effects of fetal programming in Sprague-Dawley rats through the maternal consumption of sodium saccharin on the testicular structure and function in male offspring. Feed intake and efficiency, organ and fat weight, quantification and expression of androgen receptor (AR), and proliferating cell nuclear antigen (PCNA) proteins, sperm count, and hormone levels were determined. Consumption alterations were found in the final weeks of the experiment. Decreases in AR and PCNA expression and quantification, tubular diameter, and luminal volume, and increases in epithelial and interstitial relative volumes were observed. Lower sperm count and transit, and lower estradiol concentration were also found. Sodium saccharin consumption by dams programmed male offspring by affecting the hypothalamic-pituitary-gonad axis with alterations in the Sertoli cell population, in spermatogonia proliferation, the expression and quantification of AR, and in sperm count. We hypothesized that these changes may be due to an estradiol reduction that caused the loosening of adhesion junctions of the blood-testis barrier, causing cell losses during spermatogenesis, also reflected by a decrease in tubular diameter with an increase in epithelial volume and consequent decrease in luminal volume. We conclude that maternal sodium saccharin consumption during pregnancy and lactation programmed alterations in the reproductive parameters of male offspring, thus influencing spermatogenesis.
Keywords: DOHaD; fetal programming; reproduction; sodium saccharin; sweetener; testis